Analisis Pengaruh Pemasaran dan Kepuasan Kualitas Pelayanan Terhadap Upaya-upaya Peningkatan Pendapatan UMKM di Kota Kediri Pasca Pandemi Corona Covid-19 dengan Variable Moderating Digital Marketing - Weny, Siska Yulia (Magister Manajemen Universitas Wisnuwardhana, 2025)
One of the worldwide outbreaks in 2019 was the Corona Covid-19 pandemic. The Micro, Small, and Medium Enterprises (MSMEs) sector is expected to have challenges in managing the current epidemic, according to observers. As it turns out, the use of social media for transactions is one of the elements that contribute to MSMEs' ability to withstand such circumstances. The purpose of this study is to examine the relationship between marketing and service quality satisfaction and MSME income in Kediri City, as well as the ways in which digital marketing mitigates the effects of these factors on MSME revenue. The approach is quantitative in nature. The study's findings indicate that marketing and customer satisfaction with high-quality services affect MSMEs' revenue in Kediri City. The impact of quality service satisfaction and marketing expansion on MSMEs' revenue in Kediri City is mitigated by digital marketing. In the interaction between marketing and providing high-quality services to increase revenue, digital marketing is essential. This suggests that MSMEs should use digital marketing as a means of increasing their revenue.